Factor Analysis of Socio-Economic Development of Enlarged Communities in the RA - Tatosyan, Kristine («Տնտեսագետ» հրատ․)
The administrative territorial reforms implemented in the Republic of Armenia (RA) are new challenges, which lead to the need of developing and implementing new tools aimed at local socio-economic development of communities. At this stage of the RA administrative territorial reforms, it is very important to discuss the positive or negative impact of enlargement, therefore, the assessment of the current situation by highlighting the problems, and pointing out the main ways of effectively using the available resources, can shortly contribute to increasing the efficiency of community management. Even though the enlarged communities in the RA have certain similarities in terms of expenditure directions and sources of income, we should not forget that each community also has its characteristics of socio-economic development and a unique potential for development. Within the framework of this article, based on the factor analysis of socio-economic indicators of several enlarged communities of the RA, it becomes clear that the agricultural sector is significantly separated from the production activities in Ararat, Parakar, Noyemberyan and Gavar communities, and the agricultural sector in Alagyaz and Tsaghkahovit communities does not have an impact on the local level of employment, which allows us to assume that the potential and resources in the field of agriculture are not used effectively, which in turn is due to the lack of the minimum funds necessary for the development of agriculture.
Keywords: Finance